Astra lost in space. 1, Planet camp - Shinohara, Kenta, 1974- (Shonen Jump manga., 2017)
It's the first day of Planet Camp, and Aries Spring couldn't be more excited! She, along with eight other strangers, leave for Planet McPa for a weeklong excursion. Soon after they arrive, however, a mysterious orb appears and transports them into the depths of space, where they find an empty floating spaceship--